A study of the systematic metabolism of nicotinic acid and nicotinamide in the mouse - Tanael, Susano B. Jr.
A low dose radioactive mixture of 3H-nicotinic acid and 14C-nicotimade in equal amounts was administered t mice intraperitoneally. The radioactive metabolites were then analyzed at various times. Nicotinamide and ts nucleotides predominated in the RBC and plasma, respectively. Tis could indicate that nicotinamide and nicotinamide nucelotides are the transport forms in the blood. These available forms are subsequently taken up by the peripheral organs. All the organs except the liver showed preference to nicotinamide as precursor to NAD synthesis. NAD derived from nicotinamide has a different turnover than NAD derived from nicotinic acid. Nicotinamide-derived NAD has faster turnover than nicotinic acid- derived NAD. This implies compartmentation of NAD products.
Theses--(MScience in Biochemistry) University of the Philippines Manila
Keywords: Nicotinic Acid; Nicotinamide